2012
DOI: 10.1080/01446193.2011.654233
|View full text |Cite
|
Sign up to set email alerts
|

Who gets the jobs? Factors influencing the employability of property and construction graduates in the UK

Abstract: Against a background of a strongly performing property market, the last decade saw a significant rise in entrants to undergraduate and postgraduate built environment programmes in the UK. The growth in postgraduate numbers reflected the emergence of conversion programmes with the result that, across a range of built environment pathways, employers can choose between different types of graduates: those straight from an undergraduate degree, those who have completed an additional postgraduate course or those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 12 publications
1
27
2
Order By: Relevance
“…undergraduate or postgraduate, had an impact on graduate employability as they mainly focused on studying either one type or another of the degrees. For example, Lim (2010), Smith et al (2000) focused on studying undergraduate courses while Devaney and Roberts (2012) and Urwin and Di Pietro (2005) focused on investigating employability for graduates of postgraduate courses only.…”
Section: Concluding Remarks and Identification Of Research Gapmentioning
confidence: 99%
“…undergraduate or postgraduate, had an impact on graduate employability as they mainly focused on studying either one type or another of the degrees. For example, Lim (2010), Smith et al (2000) focused on studying undergraduate courses while Devaney and Roberts (2012) and Urwin and Di Pietro (2005) focused on investigating employability for graduates of postgraduate courses only.…”
Section: Concluding Remarks and Identification Of Research Gapmentioning
confidence: 99%
“…The type of university which the graduates attended also had an influence on the employment prospects of new graduates (Devaney & Roberts, 2012;Finch et al, 2013;Urwin & Di Pietro, 2005). Urwin and Di Pietro's (2005) research found that the postgraduate students, the students who studied in Graduate School in the USA context, who graduated from institutions with a stronger research culture had and enhanced employment rate.…”
Section: Factors Related To Study Stylementioning
confidence: 99%
“…undergraduate or postgraduate, had an impact on graduate employability as they mainly focused on one type of degree. For example, Lim (2010), Smith et al (2000) focused on studying undergraduate courses while Devaney and Roberts (2012) and Urwin and Di Pietro (2005) focused on investigating employability for graduates for postgraduate courses only.…”
Section: Factors Related To Study Stylementioning
confidence: 99%
See 2 more Smart Citations